Memory and innovation in the spaces of higher education. The contribution of the architectural limit - Campos Calvo-Sotelo, Pablo; Cuenca Márquez, Fabiola (Historia y Memoria de la Educación, 2016)
The current panorama of Higher Education recommends to carry out a review of the space/time places where teaching/learning processes are hosted. The spatial consequences derived from the innovation in teaching demand the incorporation of new academic places, alternative to the traditional typology of the classroom, in order to optimize the integral formation of the student —the ultimate mission of Universities—. The historical and obsolete architectural design of the classroom, as a rigid space/time container, must start a process of de-materialization, in such a way that it fosters more versatile learning methods, that can be activated in any time and place. To accomplish such a goal, more creative ambits must be generated, adapted to a modern understanding of the idea of learning, which must abandon its old-fashion passive and static format, in order to be transformed into a dynamic modality, closed to the student and committed to him. Innovation regarding the architectural configuration is directly connected to the nature and transformation of the architectural limits which embrace and give shape to those places where formation occurs. The current demand of diversification and flexibility in learning areas must be satisfied by means of a correct articulation between the internal space of the classroom and its direct surrounding context, together with its social and cultural environment. Spatial and visual continuity generate new atmospheres that increase the quality of the teaching/learning processes. The new course of Higher Education needs a proactive review of the space/time dimensions of the traditional classroom, associated to the paradigm shift affecting modalities of teaching/learning, with the aim of generating new opportunities of innovation in Universities.